The Taiwan Voter - Wang, Te-Yu, 1957-; Achen, Christopher H.; Project Muse. (University of Michigan Press, 2017)
"The Taiwan Voter examines the critical role ethnic and national identities play in politics, utilizing the case of Taiwan. Although elections there often raise international tensions, and have led to military demonstrations by China, no scholarly books have examined how Taiwan's voters make electoral choices in a dangerous environment. Critiquing the conventional interpretation of politics as an ideological battle between liberals and conservatives, The Taiwan Voter demonstrates in Taiwan the party system and voters' responses are shaped by one powerful determinant of national identity--the China factor. Taiwan's electoral politics draws international scholarly interest because of the prominent role of ethnic and national identification. While in most countries the many tangled strands of competing identities are daunting for scholarly analysis, in Taiwan the cleavages are powerful and limited in number, so the logic of interrelationships among issues, partisanship, and identity are particularly clear. The Taiwan Voter unites experts to investigate the ways in which social identities, policy views, and partisan preferences intersect and influence each other.These novel findings have wide applicability to other countries, and will be of interest to a broad range of social scientists interested in identity politics"--
The Taiwan voter : an introduction / Christopher H. Achen and T.Y. Wang -- Who is the Taiwan voter? / Chia-hung Tsai -- Changing boundaries : the development of the Taiwan voters' identity / T.Y. Wang -- Parties, partisans, and independents in Taiwan / Ching-hsin Yu -- Issues, political cleavages, and party competition in Taiwan / Shing-yuan Sheng and Hsiao-chuan (Mandy) Liao -- Economic voting in Taiwan : micro- and macro-level analysis / Chia-hung Tsai -- Cross-strait relations and the Taiwan voter / Alex C. Tan and Karl Ho -- Evaluation of presidential candidates' personal traits / Hung-chung Wang and Lu-huei Chen -- Political left and right in Taiwan / Yi-ching Hsiao, Su-feng Cheng, and Christopher H. Achen -- Electoral system change and its effects on the party system in Taiwan / Chi Huang -- Political participation in Taiwan / Chung-li Wu with Tzu-ping Liu -- Conclusion : the power of identity in Taiwan / Christopher H. Achen and T.Y. Wang.
Includes bibliographical references and index.
Description based on print version record.
Keywords: HISTORY / Asia / Southeast Asia; POLITICAL SCIENCE / Civics & Citizenship; POLITICAL SCIENCE / Public Policy / General; Identity politics -- Taiwan; Political parties -- Taiwan; Political participation -- Taiwan; Voting research -- Taiwan; Electronic books